INNOVATIVE COOLING SYSTEM: SOLAR-POWERED WATER SPRAYERS FOR CATTLE SHEDS IN TULUNGAGUNG REGENCY - Asrori, Asrori; Nugroho, Pipit Wahyu; Yudiyanto, Eko; Witono, Kris; Buwono, Haris Puspito; Hidayat, Mohammad Noor (LPPM Univ. Ibn Khaldun Bogor, 2024)
The Community Service (CS) project was implemented in Sumberingin Kidul Village, Ngunut District, Tulungagung Regency, East Java. The target beneficiary was UD. Arta Lumintu, a local SME engaged in beef cattle farming. The farm, established in 2017, was temporarily closed due to the Covid pandemic and resumed operation after a year. Key challenges included high temperatures (24-31°C) and humidity (74-77%), which negatively impacted cattle productivity and excessive electricity consumption for cattle shed operations. The project aimed to address these issues by installing a water spray system with a high-pressure pump and an off-grid solar power system. The system effectively reduces temperature and humidity in the sheds while minimizing electricity costs. The installation consists of a 540 Wp solar panel, a 1500 VA Smart inverter, a 100 Ah VRLA battery, and six pressurized water sprinkler points positioned in various areas of the cattle sheds, powered by a 350 W booster pump. This initiative improves farm efficiency, supports energy independence, and introduces smart farming technology to benefit local farmers.